2021
DOI: 10.2166/wpt.2021.043
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological and physical quality of Fiche drinking water from households and reservoirs, Oromia, Ethiopia

Abstract: Drinking water is the major source of bacteria pathogens in developing countries along with poor sanitation and contamination of food with a pathogen. More than half of the population of the country uses unimproved sanitation facilities while 36% of them practiced open defecation. The aim of the study was to investigate the suitability of public water for drinking. The study is designed to include a survey of 90 respondents and experimental analysis of 170 water samples from households and reservoirs. Water qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…According to a report by Izah and Angaye [ 17 ], domestic waste and sewage are discharged into most surface water by communities aligning rivers. The present study is in line with the reports of Sebsibe et al [ 28 ], Hailu [ 15 ], Gadiso et al [ 13 ], Birtukan et al [ 8 ], and Amenu et al [ 5 ] which indicated that all water samples collected were positive for total coliforms and fecal coliforms. The findings of this study are also comparable to the reports of Akubuenyi et al [ 3 ], Seiyaboh et al [ 30 ], Seiyaboh and Kolawole [ 29 ], and Omoigberale et al [ 24 ].…”
Section: Resultssupporting
confidence: 93%
“…According to a report by Izah and Angaye [ 17 ], domestic waste and sewage are discharged into most surface water by communities aligning rivers. The present study is in line with the reports of Sebsibe et al [ 28 ], Hailu [ 15 ], Gadiso et al [ 13 ], Birtukan et al [ 8 ], and Amenu et al [ 5 ] which indicated that all water samples collected were positive for total coliforms and fecal coliforms. The findings of this study are also comparable to the reports of Akubuenyi et al [ 3 ], Seiyaboh et al [ 30 ], Seiyaboh and Kolawole [ 29 ], and Omoigberale et al [ 24 ].…”
Section: Resultssupporting
confidence: 93%
“…E. coli detected in over 50% of water samples from street food stalls raises concerns about potential exposure to various harmful organisms, such as Salmonella and Shigella, not covered in this study [ 54 ]. Poor environmental conditions, and the use of old and dirty containers for water transportation are common factors contributing to the presence of E. coli [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between chemical and physical parameters were analyzed to identify correlations. More general quality results like turbidity, electrical conductivity (EC), and total dissolved solids (TDS) were obtained from a previous report on the study area within the same time frame for correlation and WQI analysis (Sebsibe et al 2021).…”
Section: Discussionmentioning
confidence: 99%